1HMRS in the Hippocampus of the Female Patients with Conversion Disorder - Mermi, Osman; Baykara, Sema; Yildirim, Hanefi; Atmaca, Murad (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2021)
Introduction: Previously, we found a lower NM (N-acetyl aspartate)/CRE (creatine) ratio in conversion disorder patients, when compared to healthy controls. In this context, the present study was designed to determine the changes in hippocampal NAA, CHO (choline), and CRE values in conversion disorder female patients, which has similar symptom basement and hypothesize that the patients with conversion disorder would have also changed neurochemicals in their hippocampal regions. Method: Twenty female patients and healthy controls were included in the study. Proton magnetic resonance spectroscopy CHMRS) method was used to determine the NAA/CHO, NAA/CRE, and CHO/CRE ratios. Results: The data were analyzed via age-controlled General Linear Model and it was found that the ratio of NAA/CHO was significantly lower in conversion disorder female patients when compared to healthy controls. However, NAA/CRE or CHO/CRE ratios were similar for conversion disorder patients and healthy controls. Conclusion: It was concluded that conversion disorder female patients might have reduced NAA/CHO ratio which implicates reduced neuronal viability, possibly related to anxiety and indirectly to somatoform symptoms.
Keywords: (HMRS)-H-1; NAA; conversion disorder